Preparation and characterisation of hydrogel film and nanofiber from carboxymethyl-based cellulose and sago pulp for controlled release application - Mohd Kanafi, Nafeesa (2018)
Carboxymethyl cellulose (CMC)-based hydrogels show great capability in delivering and occupying small particles like drugs and dyes. CMC-based hydrogel could enhance the capability of a hydrogel and benefit the mankind since it has excellent biocompatibility and biodegradable properties to be use in biomedical application. In this study, a series of CMC and carboxymethyl sago pulp (CMSP) blended with poly(ethylene oxide) (PEO) hydrogel in the form of films and nanofibers were fabricated by using citric acid as a cross-linker. The CMSP used was isolated from sago waste, while CMC was purchased from Fluka Company. CMSP derived from sago waste was studied in the place of CMC because it has similar structure and can help to preserve the environment. For the production of hydrogel nanofibers, the nanofibers were prepared by using electrospinning technique prior cross-linking with citric acid. The electrospinning parameters used were concentration of the polymers blend solution, weight ratio of CMC or CMSP to PEO, applied voltage, tip-tocollector distance and the solution flow rate. The average fiber diameter of the CMSP/PEO nanofibers are from 201 to 300 nm and CMC/PEO from 101 to 200 nm. However, the formation of CMC/PEO nanofibers on the collector was very thin even after several hours of electrospinning, and not able to peel off. Thus, it cannot be further study for fabrication of hydrogel and controlled release. The swelling behaviour of the hydrogels film and nanofibers were optimised based on four parameters; ratio of CMC or CMSP to PEO, percentage of citric acid, temperature and curing time. The results show percentage of swelling and thermal property of CMC/PEO and CMSP/PEO hydrogel was improved compared to CMC and CMSP alone. In controlled release study, methylene blue (MB) was chosen as the model drug due to its hydrophilic nature. The controlled release results show CMSP/PEO hydrogel nanofibers had the highest percentage of MB loading (89.20 ± 0.42%) than CMC/PEO and CMSP/PEO hydrogels film. This can be relates with swelling results that show CMSP/PEO hydrogel nanofibers has the highest percentage of swelling (4366 ± 975%). The MB release study showed that the MB released from CMSP/PEO hydrogel nanofibers was slowly released with pH dependency. The total cumulative percentage release of MB in pH 4.0 (17.04%) and pH 7.34 (19.44%) for CMSP/PEO hydrogel nanofibers are not much different from the CMSP/PEO hydrogel film (pH 4.0 = 14.11% and pH 7.34 = 17.92%), but showed a lower total cumulative percentage release of MB at pH 1.20 (8.91%) and 8.0 (21.21%). The results indicate CMSP/PEO hydrogel nanofibers have a good potential to be used, for example for drug delivery in intestinal area and wound healing.